Ion removal performance and enhanced cyclic stability of SnO2/CNT composite electrode in hybrid capacitive deionization. (June 2020) - Wang, Shuaifeng; Wang, Shiyong; Wang, Gang; Che, Xiaoping; Li, Duanzheng; Li, Chengxu; Qiu, Jieshan
Abstract: Hybrid capacitive deionization (HCDI) is developed based on capacitive deionization (CDI) for water treatment, which combines CDI with a battery system. Developing the high-performing battery electrode materials is a significant point for HCDI. Herein, SnO2 /CNT was fabricated according to hydrothermal method, which was denoted as SnO2 /CNT-H, after calcination, the obtained product was denoted as SnO2 /CNT-HC. The as-prepared SnO2 /CNT-HC was used in HCDI system for the first time, which demonstrated a salt adsorption capacity of 9 mg g −1 and ultrafast salt adsorption rate of 2.5 mg g −1  min −1 at 500 mg L −1 initial NaCl concentration. The SnO2 /CNT-HC electrode also had a good cyclic stability of keeping 120 % of salt adsorption capacity after 100 adsorption-desorption cycles at 1.0 V and 500 mg L −1 NaCl solution. Moreover, when this system was used to study the adsorption-desorption performance for different cations (Li +, K + and Ca 2+ ) and anions (F −, NO3 − and SO4 2− ), the phenomenon was revealed that the cation adsorption capacity of Li +  > K +  > Ca 2+ captured by SnO2 /CNT-HC and the anion adsorption capacity of F −  > NO3 −  > SO4 2− adsorbed by activated carbon. These results show that SnO2 /CNT-HC should be one of realistic electrode materials for HCDI.